Rhinitis, rhinosinusutus and phytotherapy - V. V. Shilenkova (Медицинский совет, 2021)
Acute rhinitis and acute rhinosinusitis (ARS) have viral etiology in the most of cases, and their therapy is aimed at alleviating clinical symptoms and preventing new episodes. The indications for antibiotic therapy are severe bacterial ARS, ARS with complications, and recurrent bacterial ARS. Such a categorical approach is due to the increase of antibiotic resistance, which leads to the popularization of efficient phytotherapy. Modern herbal medical products comply with general recommendation and standards of efficacy, safety and quality, and their effectiveness has been proven in clinical trials along with synthetic drugs. In acute upper respiratory tract infections, herbal medical drugs stimulate the immune system, relieve clinical symptoms, and improve the patient’s quality of life. A significant emphasis in phytotherapy is given to complex drugs synthesized on the basis of phytoneering. One of such remedies is the herbal medicinal product containing the different parts of 5 medicinal herbs: Gentian root (Gentianae radix), Primrose flowers (with calyx) (Primulae flos (cum calycibus)), Common sorrel herb (Rumicis herba), Elder flowers (Sambuci flos) and Vervain herb (Verbenae herba). This herbal medicinal product shows secretolytic, secretomotor, antiinflammatory, antiviral and mild antibacterial farmacological effects. The article provides an analysis of studies in vitro and in vivo proving the anti-inflammatory effect of Sinupret®, its potentiating effect on nasal mucosa mucociliary transport as well as efficacy and safety in patients with rhinosinusitis.